Ефективність ранньої лазерної коагуляції при центральній серозній хоріоретинопатії - Безуглий, Максим Борисович; Завгородня, Наталія Григорівна; Bezugly, M. B.; Zavgorodnya, N. G. (My University, 2021)
Метою роботи було підвищення ефективності лікування гострої ЦСХ шляхом лазеркоагуляції активних точок просочування контрастної речовини Nd:YAG лазером з довжиною хвилі 561 нм в ранніх строках захворювання. Comparative analysis of focal laser coagulation of leakage points with 561 nm wavelength Nd:YAG laser at early terms of central serous chorioretinopathy with conservative treatment of the disease was carried out. Patients of the laser coagulation group had faster resorbtion of the macular edema, which was confirmed by decreasing of macular thickness at OCTscans and visual acuity improvement in two weeks after laser surgery. In one month, complete resorbtion of the macular edema was observed in 93.3 % of this group, while in the control group of patients with conservative treatment, there were no reliable changes of studied parameters even in one month after the beginning of treatment. Results of the study evidence the early use of 561 nm wavelength Nd:YAG laser coagulation to be safe and effective for acute “classic” type of central serous chorioretinopathy.
Efficacy of the early-term laser coagulation in central serous chorioretinopathy